The Effect of Customer Experience, Customer Engagement and Customer Value on Customer Loyalty on Tokopedia User - Sutrisno Sutrisno (ProBisnis : Jurnal Manajemen, 2023)
This research was conducted because the authors are interested in understanding customer experience, active involvement with customers and increasing customer perceived value as factors influencing customer loyalty in using an e-commerce service. The elements used in this research are customer loyalty, including customer experience, customer engagement, and customer value. This research methodology utilizes a quantitative approach with data collection techniques through online surveys of 103 Tokopedia users. The collected data were processed with SPSS and then analyzed using multiple regression analysis to examine the relationship between the variables studied. The results of the study show that customer experience.